The effect of provided exercise therapy on cases Morbus Hansen type multi basilers with reactions: A case report - Reyhana, Faizah Nashrillah; Arif Pristianto; Christina Wahyu Wijayanti (PT. Mega Science Indonesia, 2025)
Hansen's disease (Leprosy) is caused by Mycobacterium leprae infection and primarily affects the peripheral nervous system. Leprosy reactions, classified as type 1 (reversal) or type 2 (erythema nodosum leprosum), significantly affect sensory, motor, and functional capacities through inflammatory processes. This study evaluated the efficacy of structured exercise therapy in managing multibacillary Hansen's disease in an acute reactional state. A single-case study methodology was employed at Sumberglagah Hospital in Mojokerto, with a focus on a female patient with a leprosy reaction exhibiting movement and functional impairment. Interventions were delivered thrice weekly on alternate days, with protocol modifications on the basis of clinical status. The assessment parameters included the visual analog scale for pain, the Barthel Index for functional status, manual muscle testing for strength, anthropometric measurements for edema, goniometric evaluation for range of motion, and the prevention of disability scale for reaction severity. The intervention increased joint mobility in the hip and knee regions and significantly reduced wrist and ankle edema. Pain levels decreased in all the measured domains. However, muscle strength, functional independence scores, and overall leprosy reaction severity did not change throughout the intervention period. The Barthel Index score was maintained at 50, indicating persistent moderate dependency. Manual muscle testing demonstrated consistent values of 3/5 for most muscle groups, with selected ankle movements maintaining 4/5 strength. This severe classification reflects significant neurological involvement, which likely constrains neuromuscular recovery within the brief intervention timeframe. Exercise therapy effectively reduces pain, increases joint mobility, and resolves peripheral edema in patients with multibacillary Hansen's disease reactions, despite its limited impact on muscle strength and functional independence within the study timeframe.